2009
DOI: 10.1371/journal.pone.0005826
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Results and Conclusions of Trials of Thiazolidinediones

Abstract: BackgroundWhen a sponsor funds a study of two competing drugs in a head-to-head comparison, the results and conclusions are likely to favor the sponsor’s drug. Thiazolidinediones, oral medications used for the treatment of type 2 diabetes, are one of the most costly choices of oral anti-diabetic medications, yet they do not demonstrate clinically relevant differences in achieving lower glycosylated hemoglobin levels compared to other oral antidiabetic drugs. Our aim is to examine associations between research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Building upon the evidence that biases are common in human clinical drug studies, including studies of TZDs, funded by pharmaceutical companies,2, 10 this systematic review investigated bias in the design of TZD preclinical studies and examined the association between industry support and the outcomes. Assessment of the 112 included TZD animal studies showed evidence of poor reporting of risk of bias criteria regardless of sponsorship source, exaggerations in the effect size of efficacy and harms outcomes in industry‐sponsored studies, and non‐disclosure of funding sources (34.8%) or financial ties of investigators (83.0%) in a substantial number of articles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Building upon the evidence that biases are common in human clinical drug studies, including studies of TZDs, funded by pharmaceutical companies,2, 10 this systematic review investigated bias in the design of TZD preclinical studies and examined the association between industry support and the outcomes. Assessment of the 112 included TZD animal studies showed evidence of poor reporting of risk of bias criteria regardless of sponsorship source, exaggerations in the effect size of efficacy and harms outcomes in industry‐sponsored studies, and non‐disclosure of funding sources (34.8%) or financial ties of investigators (83.0%) in a substantial number of articles.…”
Section: Discussionmentioning
confidence: 99%
“…This instrument was modelled after previous studies that followed a similar protocol10, 11, 12, 13, 14 and included a coding manual. Methodological criteria were based on a published systematic review of tools for assessing biases in animal studies 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, numerous PTP1B inhibitors have been designed as drug candidates [18]. Thiazolidinedione (TZD) compounds class exhibit properties as antidiabetic compounds [19].…”
Section: Introductionmentioning
confidence: 99%
“…6 In 2009 researchers demonstrated that sponsored trials of new antidiabetes drugs, and trials run by authors with financial ties to companies, tended to find more favourable results for the sponsor's product: an extremely worrying finding, given the harms associated with rosiglitazone. 7 And now, in 2011, the JAMA paper suggests that the vast majority of meta-analyses fail to report such basic facts as the funding source for the original studies.…”
mentioning
confidence: 99%